The effect of rental quality (RENTQUAL) towards customer satisfaction in car rental services / Mohd Thobrani Sabdin - Sabdin, Mohd Thobrani (2019)
This study is conducted to determine the rental quality of car rental services in Sabah. RENTQUAL model will be used to measured customer’s satisfaction towards the car rental services. The attributes in this study are comfort, handling over, delivery, security, ergonomics and accessibility. This research will be based on survey carried out from online questionnaires which is through Google Form and it involves 150 respondents. The software that being used to analyse the data is IBM SPSS Statistics 25. Findings shows that delivery can be consider being concern on car rental business since it is the closest one to significant then the other. In this research it will stated the plan and suggestion to improve the quality. Thus, it is hope that the information and solution on this research will be helpful and can be utilize for future researchers and businessman.